The Indonesian Dakon Game: A Learning Method to Link Spiritual Values to Economic Praxis - Robby Igusti Chandra; Noh Ibrahim Boiliu; Budiman Widjaja (E-Journal of Humanities, Arts and Social Sciences, 2023)
Few spiritual, philosophical, and theological concepts concerning the economy have emerged especially since the Middle Age. One of them centred on the Trinitarian God concept. The concept proposes mutuality, relationship, and unity based on love and grace as shared spiritual values. The question that arises is how to educate people in applying it. This study explores whether the Dakon game, a traditional game mainly used in Java, Indonesia can be used as a learning method to apply that theological concept and their spiritual values to economic concepts and practices. The study method is literature research. The finding shows that the Dakon game causes the players to acquire a tacit knowledge that includes skills, values, and spirituality obtained through the practices of distributing wealth, sensitivity to others, and unity combined with achieving economic objectives. Although various challenges in the Indonesian context need further study, the finding can contribute to the praxis of applying spiritual values to economic praxis in Indonesia.